2022
DOI: 10.21608/ejbo.2022.124280.1921
|View full text |Cite
|
Sign up to set email alerts
|

Biological Aspects and Proline Metabolism Genes Influenced by Polyethylene Glycol and Salicylic Acid in Two Wheat Cultivars

Abstract: D ROUGHT has become an important challenge in crop cultivation, so detection of drought-tolerant cultivars by screening existing genotypes is a valuable tool in the effort to attain food security worldwide. The drought stress tolerance of two wheat cultivars was determined through treatments with PEG (−0.4MPa) and SA (0.5mM). The resulting data on seed germination and seedling growth indicated that Misr-2 cultivar is more drought-tolerant than Gemaza-12. Under non-stress conditions, Misr-2 had higher pigment v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Most of biotic and physical stimuli have demonstrated their inhibitory effect on the growth of biomass of plant cultures and the degree of the effect often varies according to the type of stimulus, its intensity and exposure time. Biotic and abiotic stresses can vigorously alter ion homeostasis, water balance, osmolyte regulation, programmed cell death and gene expression (Pareek et al, 2019;Loutfy et al, 2022;Budran et al, 2023;Drwish et al, 2023). In order to achieve sustainable production of withanolide compounds from tissue cultures, it is desirable to employ stimuli that do not exert a severe impact on plant cell growth, including their weights.…”
Section: Discussionmentioning
confidence: 99%
“…Most of biotic and physical stimuli have demonstrated their inhibitory effect on the growth of biomass of plant cultures and the degree of the effect often varies according to the type of stimulus, its intensity and exposure time. Biotic and abiotic stresses can vigorously alter ion homeostasis, water balance, osmolyte regulation, programmed cell death and gene expression (Pareek et al, 2019;Loutfy et al, 2022;Budran et al, 2023;Drwish et al, 2023). In order to achieve sustainable production of withanolide compounds from tissue cultures, it is desirable to employ stimuli that do not exert a severe impact on plant cell growth, including their weights.…”
Section: Discussionmentioning
confidence: 99%
“…Bacillus xiamenensis may increase proline synthesis in plants to help them withstand pathogen infection (Amna et al, 2020). Loutfy et al (2022) reported that, when there is a drought, proline buildup indicates plant damage brought on by stress. R. aquatilis 17 inoculations to pepper by foliar or root application caused a significant increase in total protein content while a significant reduction was associated with P. carotovorum inoculation by foliar inoculation.…”
Section: R Aquatilis Inhibited P Carotovorummentioning
confidence: 99%
“…The osmotic stress brought on by the drought brought on by the depletion of subterranean water (PEG) influences ion transport and absorption throughout the plant's life cycle, from growth to crop production (Loutfy et al, 2022). An efficient method for modifying physiological characteristics and genetic processes that result in the breeding of superior cultivars is in-vitro drought resistance screening (Mahpara et al, 2022).…”
Section: Introductionmentioning
confidence: 99%